2021
DOI: 10.18502/ijpa.v16i4.7879
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors to Lymphatic Filariasis among Residents in Igbo-Eze North; an Endemic Area in Nigeria

Abstract: Background: The study on lymphatic filariasis (LF) in Igbo-Eze North was conducted to determine the prevalence and predisposing factors to LF among its residents between May and October 2018. Methods: A total of 201 residents who have lived in the area for at least one year were recruited. They were stratified according to age, gender and occupation, and were clinically examined firstly by rapid assessment method for any lymphoedema and hydrocele. At recruitment, blood samples were collected from all vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Lymphatic filariasis in South-East, and South-South Nigeria: a microfilariae prevalence of 24.33% obtained through microscopy of Giemsa-stained thick blood smear from night samples (collected 10.00 PM-12.00 AM) was reported in three LGAs (Owerri North, Owerri West, and Ngor Okpala LGAs) of Imo State [ 51 ]. In Igbo-Eze North LGA of Enugu State, a high prevalence rate of 41.80% obtained through microscopy of Giemsa-stained thick film blood smear with associated risks of poor vector control, proximity to water bodies and lack of knowledge/awareness was reported in 4 communities [ 52 ]. Similarly, in Ebonyi State, prevalence rates of 5.38% microfilaria and 21.13% CFA with 8.23% hydrocele and 8.88% lymphedema and contraction risks of exposure to vectors and poverty were reported among inhabitants of 30 communities of Afikpo North LGA [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lymphatic filariasis in South-East, and South-South Nigeria: a microfilariae prevalence of 24.33% obtained through microscopy of Giemsa-stained thick blood smear from night samples (collected 10.00 PM-12.00 AM) was reported in three LGAs (Owerri North, Owerri West, and Ngor Okpala LGAs) of Imo State [ 51 ]. In Igbo-Eze North LGA of Enugu State, a high prevalence rate of 41.80% obtained through microscopy of Giemsa-stained thick film blood smear with associated risks of poor vector control, proximity to water bodies and lack of knowledge/awareness was reported in 4 communities [ 52 ]. Similarly, in Ebonyi State, prevalence rates of 5.38% microfilaria and 21.13% CFA with 8.23% hydrocele and 8.88% lymphedema and contraction risks of exposure to vectors and poverty were reported among inhabitants of 30 communities of Afikpo North LGA [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Along Lake Malawi shore, antigenaemia prevalence was observed to be higher compared to in-land areas, thus likely due to mosquito breeding sites driving W . bancrofti infection as well as human populations inhabiting areas close to water bodies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within these southern regions of Malawi, Nsanje and Chikwawa districts, predominantely Anopheles funestus, as well as A. arabiensis and A. gambiae have been categorised as main LF vectors [11,40]. Along Lake Malawi shore, antigenaemia prevalence was observed to be higher compared to in-land areas, thus likely due to mosquito breeding sites driving W. bancrofti infection as well as human populations inhabiting areas close to water bodies [41].…”
Section: National Lf Clinical Casesmentioning
confidence: 99%
“…Our results indicated that age, gender and duration of employment are signi cantly associated with the prevalence of LF among the respondents. Previous studies from Congo DR, South Sudan and Nigeria have implicated age and gender as strong predictors for LF prevalence and infection [23,24,25,26]. This may be due to the fact that females are more careful with their health status compared to males, therefore they (women) take necessary precautions which prevents them from unnecessary exposure to the risk of being infected with LF.…”
Section: Discussionmentioning
confidence: 99%